Analisis pada Ibu Rumah Tangga Pegiat Media Sosial Tiktok di Desa Balongdowo - Rahayu, Dhelviesarah; Hazim, Hazim (Universitas Batanghari Jambi, 2024)
This study aims to analyze the use of the tiktok social media application on the narcissistic behavior of housewives in Balongdowo Village. The method used is qualitative with a descriptive approach. The subjects in this study were housewives in Balongdowo Village. Data collection techniques are observation, interviews, and documentation. In taking informants, researchers used the purposive sampling technique, namely people who become informants are people who like to use the tiktok application with criteria that have been determined by the researcher